2014 French guidelines for hepatitis B and C screening: a combined targeted and mass testing strategy of chronic viruses namely HBV, HCV and HIV. (1st May 2016) - Bottero, Julie; Brouard, Cécile; Roudot‐Thoraval, Françoise; Deuffic‐Burban, Sylvie; Hofliger, Philippe; Abergel, Armand; Volant, Johann; Dhumeaux, Daniel; Yazdanpanah, Yazdan; ,
Abstract: Background & Aims: Worldwide and, to a lesser extent, in France, a minority of individuals infected with hepatitis B (HBV) and C (HCV) is aware of its status. Given the current availability of highly effective anti‐HBV and anti‐HCV agents, the high rate of undiagnosed people, associated with individual and community prejudices (liver disease worsening, persistence of a hidden transmission reservoir and medicoeconomic burden of delayed care), is unacceptable. Methods: On the occasion of the first French general report on viral hepatitis, new recommendations for HBV and HCV testing were issued. We aim to introduce the new French strategy for HBV and HCV screening, and to describe the underlying epidemiological data. Results: These recommendations comprise various items. First, the screening of chronic viruses, namely HBV, HCV and HIV, should be quasi‐systematically combined. Second, the targeted screening of groups at risk of viral exposure must be strengthened. Third, routine testing for each of these three viruses should be offered at least once to men of 18–60 years old who had never been tested. In parallel, in pregnant women, in addition to HIV–HBV screening, currently recommended HCV testing should be routinely performed during the first trimester of pregnancy. In order to best achieve the target populations, community initiatives that propose testing actions should be encouraged, particularly those including rapid point‐of‐care tests. Conclusions: Overall, these recommendations aim to define a comprehensive testing strategy for chronic viral infections, emphasizing both targeted screening and mass screening and considering jointly HBV, HCV and HIV.